2016
DOI: 10.21475/ajcs.2016.10.03.p7235
|View full text |Cite
|
Sign up to set email alerts
|

Development of clonal seedlings of promising Conilon coffee (Coffea canephora) genotypes

Abstract: Conilon coffee is a highly heterozygous diploid plant that is also allogamous, producing seeds through cross-fertilisation. Due to their allogamy, plants of seminiferous origin are highly heterogeneous, exhibiting high morphological and genetic diversity. However, propagation through cutting guarantees the maximum homogeneity of fields, particularly in grain maturation, among other desirable characteristics. Currently, the majority of commercial Conilon coffee is planted using seedlings propagated by cuttings.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 27 publications
5
15
0
Order By: Relevance
“…The groups formed by the UPGMA method, assuming a maximum dissimilarity limit of 50% among the genotypes, were formed similarly to those generated by Tocher's method, increasing the consistency between the clustering methods. Similarities between Tocher's and UPGMA hierarchical method were also observed by Ivoglo et al (2008), Guedes et al (2013), andCovre et al (2016), who established the maximum limits of dissimilarity among genotypes as 15%, 45%, and 50%, respectively Except for genotypes 30 and 10, all the others that represented the most dissimilar parents based on the generalized Mahalanobis distance (D 2 ) (Table III) were allocated in distinct groups by both Tocher's optimization (Table IV) and the UPGMA hierarchical method (Figure 1), increasing the reliability in the use of clusters to establish divergent combinations. Motta et al (2014) evaluated C. arabica and C. canephora genotypes and also observed that the most dissimilar genotypes based on Jaccard's index were mostly allocated in distinct groups by UPGMA.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…The groups formed by the UPGMA method, assuming a maximum dissimilarity limit of 50% among the genotypes, were formed similarly to those generated by Tocher's method, increasing the consistency between the clustering methods. Similarities between Tocher's and UPGMA hierarchical method were also observed by Ivoglo et al (2008), Guedes et al (2013), andCovre et al (2016), who established the maximum limits of dissimilarity among genotypes as 15%, 45%, and 50%, respectively Except for genotypes 30 and 10, all the others that represented the most dissimilar parents based on the generalized Mahalanobis distance (D 2 ) (Table III) were allocated in distinct groups by both Tocher's optimization (Table IV) and the UPGMA hierarchical method (Figure 1), increasing the reliability in the use of clusters to establish divergent combinations. Motta et al (2014) evaluated C. arabica and C. canephora genotypes and also observed that the most dissimilar genotypes based on Jaccard's index were mostly allocated in distinct groups by UPGMA.…”
Section: Resultssupporting
confidence: 76%
“…Studies reporting the use of Tocher's method for clustering C. canephora genotypes were also conducted by Fonseca et al (2006), who worked with 32 clones of three clonal varieties; by Ivoglo et al (2008), with 21 progenies of half-siblings; and by Covre et al (2016), with 34 promising genotypes, who reported the formation of three, four, and eight groups, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The genotypes were divided into three groups, with 41 genotypes in group 1, and the other two groups were composed of genotypes 2 and 4, respectively. The Tocher clustering method was employed by Fonseca et al (2006) when evaluating 32 clones constituting three clonal varieties forming three groups; also by Ivoglo et al (2008) with 21 progenies of half-brothers divided into four groups; and by Covre et al (2016) and Giles et al (2018) with 34 and 30 promising genotypes, in which they obtained eight and three groups, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…A study by Partelli et al (2006) proposed an equation model for conilon coffee (C. canephora) considering the length of the central vein, generating two equations according to the age of the plant, be it young or mature. However, due to the great genetic variability in C. canephora (Covre et al, 2016;Espindula et al, 2018) the plants from a specific population are heterogeneous and have distinct characteristics, and as such the revalidation of these methods becomes necessary after some time. However, the wide availability of new genotypes and their numerous distinct morphological characteristics can change the precision of the methods based on the leaf area of older genotypes (Brinate et al, 2015ab).…”
Section: Introductionmentioning
confidence: 99%